2016
DOI: 10.1111/cbdd.12847
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study on potential pharmacological activity of curcumin analogues and their copper complexes

Abstract: Curcumin and its derivatives have attracted great interest in the prevention and treatment of Alzheimer's disease, thanks both to the ability to hinder the formation of amyloid-beta (Aβ) aggregates and the ability to bind Cu (II) ion. In this article, we explore the ability of curcumin derivatives of K2T series to affect amyloid Aβ aggregation. These derivatives were obtained by introducing the t-butyl ester group through a methylenic spacer on the central carbon atom of the β-diketo moiety of curcumin frame. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Turmeric extract powder (TEP) used in this study for the production of curcumin nanoemulsion, is a mixture containing a number of commercially available vegetable supplements [ 5 ]. Among them, the pharmacological activity of curcumin, an index substance of turmeric, has been reported through many studies [ 6 , 7 , 8 ]. However, curcumin, a yellow hydrophobic polyphenolic component extracted from turmeric has limited applications due to poor solubility and toxicity at high concentrations [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Turmeric extract powder (TEP) used in this study for the production of curcumin nanoemulsion, is a mixture containing a number of commercially available vegetable supplements [ 5 ]. Among them, the pharmacological activity of curcumin, an index substance of turmeric, has been reported through many studies [ 6 , 7 , 8 ]. However, curcumin, a yellow hydrophobic polyphenolic component extracted from turmeric has limited applications due to poor solubility and toxicity at high concentrations [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, when the hydroxyl group is in para position, the inhibitory effect is reduced. Since anti-amyloid properties of several compounds have been linked to their antioxidant effects, bond dissociation energy (BDE) has been used as a parameter to compare antioxidant potency. Interestingly, when BDE was calculated for both Py-1 and Py-2, the meta-substituted compound (Py-1) displayed a lower BDE (Figure S18); therefore, Py-1 can potentially act as an antioxidant more effectively than Py-2. Interestingly, when the hydroxyl groups were completely removed (as in Py-4), amyloid inhibition was significantly reduced; however, the amyloid formation was not completely prevented most likely due to the presence of pyridazine ring and hydrogen bonding between the amino group of the inhibitor and the protein (Figure B).…”
Section: Discussionmentioning
confidence: 99%
“…Ferrari et al [40] proposed that AB31 is the best candidate for the development of new curcumin-based analogues to treat AD, due to its multifaced intrinsic characteristics which include: (i) it is able to inhibit Aβ 1-40 aggregation; (ii) it seems that it is tightly bound to Cu(II) giving more stable complexes with respect to curcumin, reducing metal concentration in the free form and, consequently, limiting Aβ 1-40 aggregation; and also (iii) AB31 is more stable than curcumin in physiological conditions, suggesting higher bioavailability. AB31 was derived by the introduction of a t-butyl ester group attached to a methylenic linker on the the β-diketo moiety of curcumin frame ( Figure 2 and Table 1).…”
Section: In Vitromentioning
confidence: 99%
“…Therefore, the complexes of gallium(III) look very promising as superoxidescavengers suggesting their possible use as SOD mimics (Figure 2 and Table 2). Additional research [40] revealed that the co-ordination of copper ion by the keto-enolic group has a protecting role since the involvement of the keto-enolic moiety in the radical delocalizationis prevented. Among the different proposed reaction mechanisms, the involvement of the keto-enolic group in stabilizing the formed radical through delocalization was also reported.…”
Section: Metal Accumulation and Metal Ion Dyshomeostasismentioning
confidence: 99%